Dynamical studies of the dissociative adsortion of some primary alkanes on Pt(111) - Cooper, Iain; McCoustra, Martin; Chesters, Michael (Ciencia, 2011)
The initial dissociative sticking coefficients, S0diss, of ethane (C2H6) and neopentane (C(CH3)4) on a Pt(111) surface at 550 K have been investigated as a function of the translational and vibrational energy content of the incident molecules using supersonic molecular beam methods. In the case of ethane, the new data are consistent with previously published data. In addition two new thresholds are observed at translational energies of ca. 35 and 60 kJ mol-1. With neopentane, a threshold is observed at around 90 kJ mol-1.